Study of mastoparan analog peptides against Candida albicans and safety in zebrafish embryos (Danio rerio) - Galeane, Mariana C. [UNESP]; Gomes, Paulo C. [UNESP]; L Singulani, Junya de [UNESP]; de Souza, Bibiana M. [UNESP]; Palma, Mario S. [UNESP]; Mendes-Giannini, Maria Js [UNESP]; Almeida, Ana Mf [UNESP] (Taylor & Francis, 2019)
Aim: In this work, mastoparan analog peptides from wasp venom were tested against Candida albicans and safety assays were performed using cell culture and model zebrafish. Materials & methods: Minimal inhibitory concentration was determined and toxicity was performed using human skin keratinocyte and embryo zebrafish. Also, permeation of peptides through embryo chorion was performed. Results: The peptides demonstrated anti-C. albicans activity, with low cytotoxicity and nonteratogenicity in Danio rerio. The compounds had different permeation through chorion, suggesting that this occurs due to modifications in their amino acid sequence. Conclusion: The results showed that the studied peptides can be used as structural study models for novel potential antifungal agents.
Keywords: antimicrobial peptides; candidiasis; chorion; mass spectrometry; mastoparans; toxicity